Wpływ Krzywizny i Podatności Ścianki na Stateczność Hydrodynamiczna Laminarnej Nieściśliwej Warstwy Przyściennej (I) - Mzyk, E. (Engineering Transactions, 1970)
In the paper a review of the previous investigations in the range of hydrodynamic stability of a laminar non-compressive flows was introduced. A historical development of the in the neighbourhood of a investigations given above was described both for the flows new rigid and flexible walls. Moreover, the consideration was given to new elements, enabling the measurements of flow stability by introducing the curvature of a wall, and, three types of non-stabilities were characterized, which might, formation appear susceptible wall-flow formation appear.